2022
DOI: 10.1186/s13223-022-00739-2
|View full text |Cite
|
Sign up to set email alerts
|

White blood cells and chronic rhinosinusitis: a Mendelian randomization study

Abstract: Background Risk factors for the pathogenesis of chronic rhinosinusitis (CRS) remain largely undetermined, which is likely due to the heterogeneity of the disease. White blood cell counts have been largely unexplored as a risk factor for CRS even though different types of white blood cells are involved in the inflammatory process of CRS. Objective To investigate causal associations between different types of white blood cells on risk of CRS utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…It deserves further investigation into which phenotypes or endotypes of CRS are more likely to be caused by GERD. Some MR studies showed that peripheral eosinophils were significantly associated with GERD, whereas there was no evidence to link neutrophils, monocytes, and lymphocytes with GERD [34]. In addition, it is unclear whether inflammatory cell counts in peripheral blood help assess the association between GERD and nasal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It deserves further investigation into which phenotypes or endotypes of CRS are more likely to be caused by GERD. Some MR studies showed that peripheral eosinophils were significantly associated with GERD, whereas there was no evidence to link neutrophils, monocytes, and lymphocytes with GERD [34]. In addition, it is unclear whether inflammatory cell counts in peripheral blood help assess the association between GERD and nasal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Phenoscanner database ( http://www.phenoscanner.medschl.cam.ac.uk/ ) was used to identify associations with confounders and outcomes. We calculated F -statistic to evaluate the strength of the instruments and F -statistic > 10 indicated sufficient strength [ 29 ]. The calculation is: F = 2 × MAF × (1− MAF ) β 2 ( N −2) / [1−2 × MAF × (1− MAF ) β 2 ], MAF is the minor allele frequency, β is the estimated corresponding effect and N is the exposure GWAS sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Phenoscanner database (http://www.phenoscanner.medschl.cam.ac.uk/) was used to identify associations with confounders and outcomes. We calculated F-statistic to evaluate the strength of the instruments and F-statistic > 10 indicated sufficient strength [29].…”
Section: Selection Of Instrumental Variablesmentioning
confidence: 99%
“…Here, we propose a new intermediate trait category for use in proxying drug targets in IMD: immune cell abundance. There is substantial animal model, observational and MR evidence [21][22][23][24][25][26] implicating immune cell dysregulation in the pathogenesis of immune-mediated disorders, ranging from roles of T H 2 cells, eosinophils, and neutrophils in allergic conditions like asthma [27,28] and eczema [29,30] to expansion of certain T helper lymphocyte and B lymphocyte lineages in autoimmune diseases such as systemic lupus erythematosus (SLE) [31], multiple sclerosis [32] and rheumatoid arthritis [5]. Furthermore, approved drug targets for IMD are usually classed as immunosuppressants or immunomodulators, which alter the balance of immune blood cells in their course of on-target action.…”
Section: Introductionmentioning
confidence: 99%